The interactions of mothers with eating disorders with their toddlers: identifying broader risk factors. Issue 4 (3rd July 2016) - Sadeh-Sharvit, Shiri; Levy-Shiff, Rachel; Arnow, Katherine D.; Lock, James D.
ABSTRACT: The connection between maternal eating disorders and feeding and eating problems among their children has been substantially demonstrated. This pilot study focused on the interactions between mothers with eating disorders and their toddlers in non-feeding situations. Twenty-eight dyads of mothers with prenatal eating disorders and their toddlers were compared to a case-matched control group with no eating disorder. Maternal current eating and co-occurring psychopathology, children's symptoms and mother–child interactions were measured. Mothers with eating disorders were less sensitive to their children, tried to control their children's behaviors more, and were less happy during mother–child interactions. The children in the maternal eating disorder group were rated as less responsive to their mothers and their mothers also reported more behavioral problems than those in the control group. Findings imply that maternal eating disorders may be linked with a wide range of adverse maternal and child behaviors beyond those associated with eating.